The Impact of Phytochemicals in Obesity-Related Metabolic Diseases: Focus on Ceramide Metabolism - Kim, Eunkyeong; Jeon, Sookyoung (Nutrients, 2023)
The prevalence of obesity and related metabolic diseases has increased dramatically worldwide. As obesity progresses, various lipid species accumulate in ectopic tissues. Amongst them, ceramides—a deleterious sphingolipid species—accumulate and cause lipotoxicity and metabolic disturbances. Dysregulated ceramide metabolism appears to be a key feature in the pathogenesis of obesity-related metabolic diseases. Notably, dietary modification might have an impact on modulating ceramide metabolism. Phytochemicals are plant-derived compounds with various physiological properties, which have been shown to protect against obesity-related metabolic diseases. In this review, we aim to examine the impact of a myriad of phytochemicals and their dietary sources in altering ceramide deposition and ceramide-related metabolism from in vitro, in vivo, and human clinical/epidemiological studies. This review discusses how numerous phytochemicals are able to alleviate ceramide-induced metabolic defects and reduce the risk of obesity-related metabolic diseases via diverse mechanisms.